Medical Expenses and Relative Weight for Diagnosis Related Groups of COVID-19 Patients Hospitalized in Rajavithi Hospital - วงศ์คำจันทร์, วรรณิศา; ภาคมฤค, ภคพร; ทองมาก, มณีรัตน์; ศิลาโรจน์, วิภรณ์รัตน์; แสงจันทร์, สายชล; เสรีรัตน์, อรศิริ (Journal of Health Science of Thailand, 2024)
Coronavirus disease 2019 (COVID-19) is a newly emerged disease causing a global pandemic with significant impacts on healthcare systems. The data on medical expenses and relative weight for diagnosis-related groups (DRG) can be utilized for planning healthcare service adjustments and resource allocation for patient care. This study aimed to analyze medical expenses and relative weight for DRG of COVID-19 patients hospitalized at Rajavithi Hospital. It was a descriptive cross-sectional study, collecting retrospective data from electronic medical records of 500 COVID-19 patients discharged from the hospital between February 2020 and July 2021. The study results showed that the majority of patients (60.8%) were female, with a median age of 41 years and a median length of stay of 12 days. Among the patients, 10.2% died, and 23.6% required admission to intensive care unit (ICU). Most patients (53.8%) had moderate disease severity. The total medical expenses amounted to 105,368,881.70 baht. The median medical expenses for severe cases were 335,913.13 baht, for moderate cases 143,833.00 baht, and for mild cases 83,460.00 baht (with median AdjRW of 3.9531, 0.5931, and 0.4668, respectively). Additionally, the study found that patients with different ages, lengths of stay, types of wards admitted to, discharge types, discharge statuses, severity levels, and virus strains had significantly different medical expenses and AdjRW (p<0.05). Patients with comorbidities at risk for severe COVID-19 had significantly higher medical expenses and AdjRW than those without comorbidities (p<0.05). The medical expenses for severe cases were 4.02 times higher than for mild cases, and the AdjRW was 8.47 times higher. In conclusion, most COVID-19 patients had moderate symptoms without complications. The medical expenses per admission were 143,970.00 baht, and the AdjRW was 0.5931.